THE IMPORTANCE OF PRESCHOOL EDUCATION IN THE EDUCATIONAL SYSTEM OF UZBEKISTAN - Muminova Gulasal Bakhodirovna,; Qurbonova Ruxshona, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the role of preschool education in the system of continuing education.